TINJAUAN KRITIS KONSERVASI TEKSTIL KOLEKSI JUBAH SULTAN THAHA MUSEUM KEBANGKITAN NASIONAL - Fitri, Zulfa Nurdina; Akbar, Ali (Paradigma: Jurnal Kajian Budaya, 2024)
A museum plays a central role in conserving cultural heritage. Hence, conserving museum collections is pivotal for preserving the values of the collection. The museum of National Awakening has a potential national collection that requires curative conservation due to its damaged condition, i.e., Sultan Thaha Robes. However, the conservation effort lacked written and visual documentation of the collection due to the collection's urgency, causing it difficult for conservators to access the conservation-related information. This paper presents a critical review of conservation stages performed on Sultan Thaha Robes while suggesting a complete, systematic conservation solution based on the theoretical collaboration of textile conservation experts.